2014
DOI: 10.1016/j.jaci.2013.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Component resolution reveals additional major allergens in patients with honeybee venom allergy

Abstract: Analysis of a panel of CCD-free HBV allergens improved diagnostic sensitivity compared with use of rApi m 1 alone, identified additional major allergens, and revealed sensitizations to allergens that have been reported to be absent or underrepresented in therapeutic HBV preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
206
4
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(228 citation statements)
references
References 34 publications
8
206
4
10
Order By: Relevance
“…[104][105][106] It also appears that the broad sensitization pattern in honeybee venom-allergic patients may play a role in the lower effectiveness of honeybee VIT. 107 For example, some patients are predominantly sensitized to Api m 10, which may be underrepresented in certain available honeybee venom preparations. …”
Section: Adherencementioning
confidence: 99%
“…[104][105][106] It also appears that the broad sensitization pattern in honeybee venom-allergic patients may play a role in the lower effectiveness of honeybee VIT. 107 For example, some patients are predominantly sensitized to Api m 10, which may be underrepresented in certain available honeybee venom preparations. …”
Section: Adherencementioning
confidence: 99%
“…Four and 8 patients were administered a maintenance dose of 100 μg Api m 1 is the dominant sensitizer in patients with HBV allergy, regardless of whether the native [6] or recombinant [4,5] antigen is used. In the present study, nApi m 1 was recognized by 100% of patients, who were divided into 2 phenotype groups on the basis of a cutoff of 0.35 kU/L.…”
Section: Clinical Changes Bvit Safetymentioning
confidence: 99%
“…The combined use of these 3 components, which make up the bulk of the dry weight of venom, was found to increase diagnostic performance by 15% compared with the use of rApi m 1 alone [9]. A later study using 6 different HBV components showed the complexity of sensitization profiles in patients with HBV allergy [4].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations